2002
DOI: 10.1074/jbc.m111305200
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidized Lipid and Lipoxygenase Product 12(S)-Hydroxyeicosatetraenoic Acid Induces Hypertrophy and Fibronectin Transcription in Vascular Smooth Muscle Cells via p38 MAPK and cAMP Response Element-binding Protein Activation

Abstract: Growth factor-and cytokine-induced vascular smooth muscle cell proliferation, migration, hypertrophy, and matrix production have been shown to play important roles in the development of vascular disorders such as atherosclerosis, hypertension, and restenosis. Growth factors such as angiotensin II (AngII) 1 and platelet-derived growth factor (PDGF) activate intracellular phospholipases, leading to the formation of arachidonic acid, which can be further metabolized by cyclooxygenases, cytochrome P-450 oxygenases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
137
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 57 publications
13
137
0
Order By: Relevance
“…25,26 Furthermore, p38 MAPK activity was augmented in rat VSMC and cardiac fibroblasts overexpressing 12-LO cells. 25,34 Hence, we hypothesized that p38 MAPK activation may be reciprocally attenuated in LOKO VSMC. MVSMC were stimulated with serum (10% FBS) and cell lysates immunoblotted with phosphospecific-p38 MAPK antibody.…”
Section: Reduced Activation Of P38 Mapk In Loko Mvsmcmentioning
confidence: 96%
See 2 more Smart Citations
“…25,26 Furthermore, p38 MAPK activity was augmented in rat VSMC and cardiac fibroblasts overexpressing 12-LO cells. 25,34 Hence, we hypothesized that p38 MAPK activation may be reciprocally attenuated in LOKO VSMC. MVSMC were stimulated with serum (10% FBS) and cell lysates immunoblotted with phosphospecific-p38 MAPK antibody.…”
Section: Reduced Activation Of P38 Mapk In Loko Mvsmcmentioning
confidence: 96%
“…22,24 Recently, we showed that 12-LO products directly stimulated VSMC hypertrophy, activation of p38 mitogen-activated protein kinase (p38 MAPK), transcription factors NF-kappa B (NF-B), and cAMP response element binding protein (CREB) and induced transcription from the fibronectin and VCAM-1 promoters. 25,26 Furthermore, stable 12/15-LO overexpression in VSMC increased MAPK activity and induced hypertrophy. 25 Thus, 12/15-LO activation in VSMC may play a key role in vascular growth and injury responses.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Reddy et al 6 previously demonstrated that 12S-HETE induces fibronectin promoter activity in VSMCs. To determine whether 12/15LO increases fibronectin production in vivo, potentially contributing to increased NIF in 12/15LO-tg mice, we performed immunostaining for fibronectin on 28-day postinjury LCCA sections (8 animals in each group).…”
Section: /15lo-tg Mice Have More Neointimal Fibronectin Deposition mentioning
confidence: 98%
“…12/15LO products of arachidonic acid, such as 12S-hydroxyeicosatetrenoic acid (HETE), 15S-HETE, and 13S-hydroperoxyoctadecadienoic acid (HPODE), are produced in VSMCs and have hypertrophic effects. 5,6 In vitro, 12/15LO inhibition attenuates hypertrophic effects of angiotensin II in VSMCs, mitogenic effects of cytokines, and chemotactic effects of platelet-derived growth factor. 5,7,8 Compared with VSMCs from C57BL/6 (BL-6) mice, VSMCs from 12/15LO-overexpressing transgenic (12/15LO-tg) mice grow faster, and VSMCs from 12/15LO Ϫ/Ϫ mice grow slower and display decreased S-phase entry in culture.…”
mentioning
confidence: 99%